POPOSED MECHNISM FOR INSTITUTIONAL COORDINATION BETWEEN AGRICULTURAL EXTENTION , RESEARCHES ORGANIZATION AND AGRICULTURAL SERVES ORGANIZATIONS OPERATING IN THE GOVERNORATE OF HOLY KARBALA - AL - atwany, Ismail & (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The research Milled I building proposed mechanism for institutional coordination between apicultural research and agricultural service ordain Faction operating in the و agricultural extension Governorate of Karbala, In order to achieve the objectives of the research, a questionnaire was prepared, including a five point scale consisting of (120) items distributed on (5) fields and (9) axes, the research was carried out in Karbala governorate on a random sample of 24 % of the research Community, which is composed of 524 respondents thus the research sample become 126 respondents. By presenting the proposed mechanism on the sample of the research, the final forum was Weight mean greater reached using the following standard: the item remains in the final form if it get a than the proposed mean announced 3 degree. The result was survival of all the items within the final Construction of the coordination mechanism, as the field of evaluation ranked first in weighted mean of (4 . 27degree, and then the implementation field with mean of 4. 264 degree, then the monitor field weighted mean of 4. 24 degree, then the planning field with weighted mean of 4 . 2l degree, the field of organization carne last with weighted mean of 4 . 18 degree . The researcher recommends adopting the proposed mechanism in order to unite the possibilities and not to waste time and effort and reduce the cost and prevent conflict in the work of all parties related to Agricultural and rural development, bicultural service agencies